Two-Stage Total Hip Arthroplasty for Severe Hip Joint Destruction in SAPHO Syndrome: A Case Report - Meshram, Vaishnavi; Sakharwade, Prerna (Nursing Case Insight Journal, 2025)
The syndrome of synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) is becoming more well-known. The hip joint is a less commonly afflicted location in SAPHO syndrome, and there have been few reports of hip joint illnesses caused by SAPHO syndrome, thus effective treatment for this disease spectrum is yet unknown. The case of a 22-year-old man who was hospitalized for SAPHO syndrome and later diagnosed with advanced secondary hip arthritis and severe right hip pain is described. The identification of SAPHO syndrome was delayed; in a prior tertiary health center, the patient was diagnosed with osteomyelitis and treated with extensive courses of antibiotics and open surgical debridement. In our facility, the patient had two stages of joint replacement surgery. He is doing well a year after surgery, with minor right hip discomfort and a functional prosthesis. This case demonstrates the safety and efficacy of a two-stage joint replacement in the treatment of degenerative hip disease caused by SAPHO syndrome, which mimics infectious arthritis